Effects of isolation, crowding, and different psychological countermeasures on crew behavior and performance - Shved, Dmitry; Kuznetsova, Polina; Rozanov, Ivan A.; Lebedeva, Svetlana A.; Vinokhodova, Alla; Savinkina, Alexandra; Shishenina, Ksenia; Rey, Nicole Diaz; Gushin, Vadim (Frontiers in Physiology, 2022)
Studies made by I. Altman in the 1960–70s revealed the increase of individual stress level under isolation and confinement. Altman introduced the term “privacy” as a desired level of personal space that humans need to feel psychologically comfortable. The author also mentioned the dynamic process of boundaries regulation that can be accompanied by the increase of conflict tension in the confined groups. In our study with short-term chamber isolation ESKIS, we analyzed behavior, crew interactions and psychological state of the mixed gender crew with none or minimal previous isolation experience (4 male and 2 female) who spent 14 days in the small chamber of 50 m3. The study confirmed that the pre-isolation period was especially stressful for the subjects who felt significant anxiety also during the first days of isolation. Also, some mood and sleep disturbances were detected under isolation and crowding. Psychological stress made the crew more cohesive, they demonstrated the increase of the common values. Extraverted subjects who could obtain social support from their partners and Mission Control’s duty teams were less interested in psychological support via VR.